hi solve this question
use a^3+b^3= (a+b)(a^2-ab+b^2) formula
Attachments:
![](https://hi-static.z-dn.net/files/db9/3ccb48c773de993003bd9bcb2630e715.jpg)
Answers
Answered by
4
Answer:
QED
Step-by-step explanation:
Sin^6θ + cos^6θ + 3Sin^2θCos^2θ
= (sin^2θ+Cos^2θ)(Sin^4θ-Sin^2θCos^2θ+Cos^4θ) + 3sin^2θCos^2θ
Using a^3+b^3= (a+b)(a^2-ab+b^2) a = Sin^2θ b = Cos^2θ
as sin^2θ + Cos^2θ = 1
= Sin^4θ +2sin^2θCos^2θ+Cos^4θ
= (sin^2θ + Cos^2θ)^2
= 1^2
= 1
QED
= 1
amitnrw:
mark as brainliest if u liked
Answered by
2
Answer:
1
Step-by-step explanation:
Given Equation is sin⁶θ + cos⁶θ + 3sin²θcos²θ
= (sin²θ)³ + (cos²θ)³ + 3sin²θcos²θ
= (sin²θ + cos²θ)(sin⁴ + cos⁴θ - sin²θcos²θ) + 3sin²θcos²θ
= (sin²θ + cos²θ)[sin⁴θ + cos⁴θ - sin²θcos²θ + 3sin²θcos²θ]
= (1)[sin⁴θ + cos⁴θ + 2sin²cos²θ]
= (sin²θ)² + (cos²θ)² + 2(sin²θ)(cos²θ)
= (sin²θ + cos²θ)²
= 1.
Hope it helps!
Similar questions